2016
DOI: 10.1371/journal.pone.0156851
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Diet Quality and Acculturation of Immigrated South Asian American Adults and Their Association with Metabolic Syndrome

Abstract: Even though the total SA American population is increasing rapidly, there is a paucity of information on the relationship between diet quality, acculturation and health outcomes such as Metabolic Syndrome (MetS) in the low-income South Asian (SA) sub-population. Our goal was to examine diet quality, degree of acculturation and their potential influence on MetS in a diverse sample of SA Americans. A convenience sample of 401 adult SA men and women were studied using a cross-sectional study design. Volunteers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Since Hispanic/Latinos and non‐Hispanic blacks have similar socioeconomic profiles, this supports the argument that diet choices are influenced by factors other than income and education. Our finding that men had a better quality diet than women differs from the US general population, but conforms with the Multiethnic Cohort study, in which a higher proportion of women than men had 2010 AHEI scores in lowest quartile and conforms with a study of South Asian immigrants to the United States, in which men's diets were of better diet quality than women's …”
Section: Discussionsupporting
confidence: 88%
“…Since Hispanic/Latinos and non‐Hispanic blacks have similar socioeconomic profiles, this supports the argument that diet choices are influenced by factors other than income and education. Our finding that men had a better quality diet than women differs from the US general population, but conforms with the Multiethnic Cohort study, in which a higher proportion of women than men had 2010 AHEI scores in lowest quartile and conforms with a study of South Asian immigrants to the United States, in which men's diets were of better diet quality than women's …”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with other studies that reported a decrease in dietary quality after immigration [ 9 10 11 ]. In the current study, Vietnamese women immigrants had decreased DQI-I and moderation scores, as well as a decreased DDS score, which indicates dietary adequacy, after immigration than before immigration, even though the variety score of DQI-I increased.…”
Section: Discussionsupporting
confidence: 93%
“…An earlier study reported less acculturated South Asian Americans had a lower diet quality and greater incidence of metabolic syndromes than more accultured South Asian Americans [ 10 ]. A previous study reported that Vietnamese women immigrants have little opportunity to eat Vietnamese food and more than 80% of subjects consume Korean dishes at every meal [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous dietary analysis of SA, (Khan, Jackson, & Momen, ) calculated the National Cancer Institute healthy eating index scores and a fatty acid score (worth 10 points) was a part of that overall score. They reported gender differences among the fatty acid scores for those with MetS.…”
Section: Discussionmentioning
confidence: 99%